The Incidence of U.S. Agricultural Subsidies on Farmland Rental Rates - Kirwan, Barrett E. (Journal of Political Economy, 2009)
Who benefits from agricultural subsidies is an open question. Economic theory predicts that the entire subsidy incidence should be on the farmland owners. Using a complementary set of policy quasi experiments, I find that farmers who rent the land they cultivate capture 75 percent of the subsidy, leaving just 25 percent for landowners. This finding contradicts the prediction from neoclassical models. The standard prediction may not hold because of less than perfect competition in the farmland rental market; the share captured by landowners increases with local measures of competitiveness in the farmland rental market.